2022
DOI: 10.3390/poultry1020008
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation with Pomegranate and Onion Aqueous and Cyclodextrin Encapsulated Extracts Affects Broiler Performance Parameters, Welfare and Meat Characteristics

Abstract: The purpose of this trial was to evaluate the effects of Punica granatum L. and Allium cepa L. peels aqueous and cyclodextrin extracts on broiler chicks’ performance and welfare status, as well as on the meat chemical composition and oxidative stability. A total of 120 one-day-old male Ross-308 chicks were randomly allocated to three treatments with four replicate pens (10 chicks per pen). Broiler chicks in the control group were fed typical commercial rations in mash form, based on maize and soybean meal. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…The addition of 2% garlic powder for 42 days resulted in a higher final body weight than the control (control: 1949.5 g; 2% garlic powder: 2019.0 g) [ 55 ]. However, some studies have shown comparable broiler productivity despite the addition of various types (e.g., garlic powder, garlic extract, chive extract, and onion peel aqueous extract) of plants of the genus Allium [ 56 , 57 , 58 , 59 , 60 , 61 ]. In the results of this study, when the CC additive was mixed with feed, it showed no significant difference in productivity with enramycin, a poultry growth promoting antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of 2% garlic powder for 42 days resulted in a higher final body weight than the control (control: 1949.5 g; 2% garlic powder: 2019.0 g) [ 55 ]. However, some studies have shown comparable broiler productivity despite the addition of various types (e.g., garlic powder, garlic extract, chive extract, and onion peel aqueous extract) of plants of the genus Allium [ 56 , 57 , 58 , 59 , 60 , 61 ]. In the results of this study, when the CC additive was mixed with feed, it showed no significant difference in productivity with enramycin, a poultry growth promoting antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…The results were expressed as mg gallic acid equivalents (GAE)/g plant material. A method described by Vasilopoulos et al, (2022), was applied to determine antiradical activity. Trolox TM was used to create a standard curve, and the results were presented as μmol Trolox equivalents (TRE)/ g plant material (mM TRE).…”
Section: Determination Of Total Phenolic Content (Tpc) and Dpph Radic...mentioning
confidence: 99%
“…Diarrhea scores were evaluated on day 10, on 2 birds per pen, using categories from 1 to 3 (where 1 indicates absence of diarrhea and 3 severe diarrhea). On days 10, 24 and 35, fecal scores were evaluated on surface per pen, using categories from 1 to 4 (where 1 represents firm and well-formed feces and 4 represents watery liquid feces) (Vasilopoulos et al, 2022). On days 10, 24 and 35, litter scores were evaluated on 2 samples, coming from pooled samples of 3 locations per pen, using categories from 1 to 5 (where 1 illustrates dry and crumbly litter and 5 illustrates capping or completely wet litter).…”
Section: Welfare Statusmentioning
confidence: 99%
See 2 more Smart Citations